Species Composition and Tree Structure at Various Altitudes in Gunung Halimun Salak National Park - Istomo; Hartoyo, Adisti Permatasari Putri; Azizah, Ummiati (Journal of Tropical Silviculture, 2024)
rainforest ecosystems. This study aimed to estimate the species composition and tree structure at various altitudes in GHSNP. The study used vegetation analysis through plots measuring 100 m × 20 m with three replications at three altitude ranges: <1000 masl (lowland), 1000-1500 masl (sub-montane), and >1500 masl (montane). At altitudes <1000 and 1000-1500 masl, Pinus merkusii and Schima wallichii are the dominant species, while Dacrycarpus imbricatus dominates at altitudes >1500 masl. The total volume of trees at each altitude range is 473.9 m3/ha, 221.67 m3/ha, and 201.11 m3/ha, respectively. As altitude increases, tree volume decreases. The species diversity index (H') value at all three altitudes is classified as medium, with a 1≤H'≤3 value. Keywords: Dacrycarpus imbricatus, Pinus merkusii, Schima wallichii, West Java